Supporting people in mental health crisis in 21st-century Britain. (December 2020) - Molodynski, Andrew; Puntis, Stephen; Mcallister, Em; Wheeler, Hannah; Cooper, Keith
Abstract : Recent years have seen a surge in interest in mental healthcare and some reduction in stigma. Partly as a result of this, alongside a growing population and higher levels of societal distress, many more people are presenting with mental health needs, often in crisis. Systems that date back to the beginning of the National Health Service still form the basis for much care, and the current system is complex, hard to navigate and often fails people. Law enforcement services are increasingly being drawn into providing mental healthcare in the community, which most believe is inappropriate. We propose that it is now time for a fundamental root and branch review of mental health emergency care, taking into account the views of patients and the international evidence base, to 'reset' the balance and commission services that are humane and responsive – services that are fit for the 21st century.